2006
DOI: 10.1063/1.2179407
|View full text |Cite
|
Sign up to set email alerts
|

High quality step-edge substrates for high-Tc superconducting devices

Abstract: Despite the significant progress in fabrication methods of step edge, the lack of reproducibility still hinders their use in more complicated systems. To pursue the high reproducibility and quality of step edge for high-Tc superconducting devices, we have developed the technique to fabricate high quality step-edge substrates with arbitrary step angles. We used two steps to improve the step ramp quality substantially. The surface microscopy of step substrates shows high uniformity with respect to any step angle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…A second etching step was found to significantly improve the profile of the etched steps by cleaning the surface prior to YBCO film deposition [16]. Other workers have subsequently found this second etching step useful [21].…”
Section: Introductionmentioning
confidence: 99%
“…A second etching step was found to significantly improve the profile of the etched steps by cleaning the surface prior to YBCO film deposition [16]. Other workers have subsequently found this second etching step useful [21].…”
Section: Introductionmentioning
confidence: 99%
“…A proposed design of serial SQUID arrays has significantly improved the fabrication [82] yield. High quality bi-crystal [83], step-edge substrates [84] and high quality YBa 2 Cu 3 O y films are required to achieve high fabrication yields.…”
Section: Challenges and Perspectivementioning
confidence: 99%
“…[8] In particular, we note that Wu et al investigated the influence of the step angle on the fabrication of YBCO DC SQUIDs with SEJs. [9] Using MgO as the substrate material, they reported a SQUID having white flux noise around 60 µΦ 0 / √ Hz. As for the ratio of the film thickness d to the step height h, d/h, the previous studies indicated that it should have a value between 2/3 and 1 for PLD-grown YBCO films and about 1/2 for sputtered ones.…”
Section: Introductionmentioning
confidence: 99%